2023
DOI: 10.3389/fpubh.2023.1132575
|View full text |Cite
|
Sign up to set email alerts
|

The rapid change in mental health among college students after introduction of on-campus quarantine during the 2022 Shanghai COVID-19 lockdown

Abstract: ObjectivesAmong the various impacts of disasters in terms of emotions, quarantine has been proven to result in significant increases in mental health problems. Studies of psychological resilience during outbreaks of epidemics tend to focus on long-term social quarantine. In contrast, insufficient studies have been conducted examining how rapidly negative mental health outcomes occur and how these outcomes change over time. We evaluated the time course of psychological resilience (over three different phases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…A recent study reported that 21.1% undergraduate and postgraduate college students (aging 18 years and older) from 152 countries reported depression [16]. In Shanghai, depressive symptoms dramatically increased in college students with the introduction of quarantine in periods 2 and 3 compared to period 1 [17]. A similar observation was found in a study conducted in Poland, with elevated stress and lower general health in University students during the pandemic [18].…”
Section: Introductionsupporting
confidence: 61%
“…A recent study reported that 21.1% undergraduate and postgraduate college students (aging 18 years and older) from 152 countries reported depression [16]. In Shanghai, depressive symptoms dramatically increased in college students with the introduction of quarantine in periods 2 and 3 compared to period 1 [17]. A similar observation was found in a study conducted in Poland, with elevated stress and lower general health in University students during the pandemic [18].…”
Section: Introductionsupporting
confidence: 61%
“…Liu et al, 2022b). With mobility restrictions, students have lost previous autonomy of movement (Ma et al, 2023), as activities become confined to campus and dormitories (W. Zhang et al, 2023). In this constrained environment, students' mental well-being becomes increasingly vulnerable.…”
Section: Introductionmentioning
confidence: 99%